The Impact Of Investment Business In The Plantation Sector On Increasing Community Welfare In Keerom District - Herniati Herniati (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2022)
Regency, especially the plantation sector, namelyincreasing the welfare of the community around thecompany. The method used in this research wasqualitative research. This research is to find out andexplain the forms of cooperation between investmentcompanies and the people of Keerom Regency inimproving the welfare of the community aroundinvestment companies in the plantation sector. And,to find out the efforts to empower the communityaround the Planting Company in improving people'swelfare. The purpose of implementing investment isto improve the welfare of the community and createemployment opportunities to benefit the region,provide benefits to the community around thecompany through community empowerment(Community Development), and provide benefitstoplantation business actors